Obstructive Sleep Apnea Susceptibility Genes in Chinese Population: A Field Synopsis and Meta-Analysis of Genetic Association Studies - Sun, Jinxian (PLoS One, 2015)
BACKGROUND: Epidemiological studies to date have evaluated the association between genetic variants and the susceptibility to obstructive sleep apnea (OSA). However, the results of these studies have been inconclusive. In this current study we performed meta-analysis of genetic association studies (GAS) to pool OSA-susceptible genes in Chinese population, to perform a more precise evaluation of the association. METHODS: Various databases (i.e., PubMed, EMBASE, HuGE Navigator, Wanfang and CNKI) were searched to identify all eligible GAS-related variants associated with susceptibility to OSA. The generalized odds ratio metric (OR(G)) and the odds ratio (OR) of the allele contrast were used to quantify the impact of genetic variants on the risk of OSA. Cumulative and recursive cumulative meta-analyses (CMA) were also performed to investigate the trend and stability of effect sizes as evidence was accumulated. RESULTS: Thirty-two GAS evaluating 13 polymorphisms in 10 genes were included in our meta-analysis. Significant associations were derived for four polymorphisms either for the allele contrast or for the OR(G). The variants TNF-α-308G/A, 5-HTTLPR, 5-HTTVNTR, and APOE showed marginal significance for OR(G) (95% confidence interval [CI]): 2.01(1.31–3.07); 1.31(1.09–1.58); 1.85(1.16–2.95); 1.79(1.10–2.92); and 1.79(1.10–2.92) respectively. In addition, the TNF-α-308G/A, 5-HTTLPR, and 5-HTTVNTR variants showed significance for the allele contrast: 2.15(1.39–3.31); 2.26(1.58–3.24); 1.32(1.12–1.55); and 1.86(1.12–3.08) respectively. CMA showed a trend towards an association, and recursive CMA indicated that more evidence was needed to determine whether this was significant. CONCLUSIONS: TNF-α, 5-HTT, and APOE genes can all be proposed as OSA-susceptibility genes in Chinese population. Genome-wide association studies (GWAS) are therefore urgently needed to confirm our findings within a larger sample of OSA patients in China.